2017
DOI: 10.1093/annonc/mdx359
|View full text |Cite
|
Sign up to set email alerts
|

First-line icotinib versus cisplatin/pemetrexed plus pemetrexed maintenance therapy for patients with advancedEGFR mutation-positive lung adenocarcinoma (CONVINCE): a phase 3, open-label, randomized study

Abstract: First-line icotinib significantly improves PFS of advanced lung adenocarcinoma patients with EGFR mutation with a tolerable and manageable safety profile. Icotinib should be considered as a first-line treatment for this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
199
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(222 citation statements)
references
References 19 publications
12
199
2
Order By: Relevance
“…The prognosis of patients with advanced non-small cell lung cancer (NSCLC) harboring epidermal growth factor receptor (EGFR) mutations has dramatically changed in the last years as a result of the incorporation of targeted therapies with tyrosine kinase inhibitors (TKIs) into the first line, resulting in much better tolerated treatments than standard chemotherapy and improved response rates and progression-free survival (PFS) [3,4,5,6,7,8,9]. Although overall survival (OS) has clearly increased when compared with historical data from the pre-targeted therapy era, randomized trials of TKIs versus chemotherapy have not shown an OS advantage for EGFR-mutant patients, mainly due to the treatment crossover at progression, with the exception of the subset of patients with exon 19 deletion treated with the TKI afatinib [10].…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of patients with advanced non-small cell lung cancer (NSCLC) harboring epidermal growth factor receptor (EGFR) mutations has dramatically changed in the last years as a result of the incorporation of targeted therapies with tyrosine kinase inhibitors (TKIs) into the first line, resulting in much better tolerated treatments than standard chemotherapy and improved response rates and progression-free survival (PFS) [3,4,5,6,7,8,9]. Although overall survival (OS) has clearly increased when compared with historical data from the pre-targeted therapy era, randomized trials of TKIs versus chemotherapy have not shown an OS advantage for EGFR-mutant patients, mainly due to the treatment crossover at progression, with the exception of the subset of patients with exon 19 deletion treated with the TKI afatinib [10].…”
Section: Introductionmentioning
confidence: 99%
“…Epidermal growth factor receptor ( EGFR ) gene mutations occur in approximately 50% of Asian non‐small cell lung cancer (NSCLC) patients, particularly in never‐smokers and patients with adenocarcinoma . First‐line treatment with reversible first‐generation EGFR tyrosine kinase inhibitors (TKIs), such as gefitinib, erlotinib, and icotinib, and second‐generation EGFR TKIs (afatinib) have been shown to improve progression‐free survival (PFS) in NSCLC patients with EGFR ‐sensitive mutations compared with chemotherapy . However, despite the good initial responses of these first‐ and second‐generation EGFR TKIs, most patients develop acquired resistance.…”
Section: Introductionmentioning
confidence: 99%
“…2 First-line treatment with 594 reversible first-generation EGFR tyrosine kinase inhibitors (TKIs), such as gefitinib, erlotinib, and icotinib, and second-generation EGFR TKIs (afatinib) have been shown to improve progression-free survival (PFS) in NSCLC patients with EGFR-sensitive mutations compared with chemotherapy. [3][4][5][6][7][8] However, despite the good initial responses of these firstand second-generation EGFR TKIs, most patients develop acquired resistance. Moreover, there has been no evidence that patients benefit from the sequential use of different first-generation EGFR TKIs.…”
Section: Introductionmentioning
confidence: 99%
“…Despite high tumor response rates with first‐line EGFR‐TKIs, the majority of patients acquire resistance to first‐generation EGFR‐TKIs within a year . It is estimated that 50–60% of patients develop T790M mutations .…”
Section: Introductionmentioning
confidence: 99%
“…Despite high tumor response rates with first-line EGFR-TKIs, the majority of patients acquire resistance to firstgeneration EGFR-TKIs within a year. [5][6][7] It is estimated that 50-60% of patients develop T790M mutations. 8 For T790M positive patients, osimertinib is more effective than chemotherapy; 9 however, cytotoxic chemotherapy is still the best choice for T790M negative patients.…”
Section: Introductionmentioning
confidence: 99%